P583 Ustekinumab during pregnancy in patients with inflammatory bowel disease: a prospective multicenter cohort study. (21st January 2022) - Avni Biron, I; Mishael, T; Zittan, E; Livne, M; Zinger, A; Tzadok, R; Goldenberg, R; Kopylov, U; Ron, Y; Hadar, E; Helman, S; Ollech, J; et al.
Abstract: Background: The prevalence of inflammatory bowel diseases (IBD) is high in women of childbearing age. Maintaining remission from conception to delivery is associated with improved pregnancy outcomes, and continued drug therapy throughout pregnancy is often needed. Data regarding pregnancy outcomes in patients with IBD treated with ustekinumab (UST) are limited. We aimed to assess maternal, pregnancy, and neonatal outcomes in patients with IBD treated with ustekinumab (UST). Methods: In a multicenter, prospective, cohort study, women with IBD treated with UST during conception and pregnancy were recruited between 2019–2021. Outcomes were compared between patients treated with: UST, anti-tumor necrosis factor (TNF)-a, and non-UST, non anti-TNF therapy (thiopurines or mesalazine) or no therapy. UST treated patients were matched to controls in a 1:2 ratio according to age, BMI, and number of previous pregnancies. Newborns were followed up-to 12 months. Results: Pregnant patients recruited: 129, 27-UST; 52- anti-TNF; 30-non-UST, non anti-TNF 20- no therapy (the latter 50=conventional control group). The vast majority (96.9%) had Crohn's disease (CD). Patients treated with UST compared to those treated with anti-TNF or conventional therapy, showed a trend towards longer disease duration (11 vs 7 vs 6 years, respectively, p=0.06), higher proportion of smokers (30.8% vs 5.9% vs 0%, respectively, p<0.001), higher rate of previous exposure to infliximab(77.8% vs 52.0% vs 14.5%, p<0.001), adalimumab (92.6% vs 66.7% vs 22.0%, p<0.001), and vedolizumab (48.1% vs 5.8% vs 4.0%, p<0.001) and higher rate of disease activity at conception (59.3% vs 15.4% vs 8%, p<0.001). Most of the patients treated with UST(n=25, 92.5%), continued therapy throughout pregnancy. New flares during pregnancy were comparable (15.2% vs 45.5% vs.39.4%, p-0.92). Among UST-treated patients, pregnancy outcomes included: two spontaneous abortions, 4% of of preterm labor and low birth weight, one congenital anomaly (tetralogy of Fallot) (4%), and 42% cesarean section. Maternal outcomes, specifically obstetric complications and hospitalizations, pregnancy, and neonatal outcomes were comparable between treatment groups. Rates of newborn 1st-year infections, hospitalizations, and developmental delay were also comparable. Conclusion: Pregnant patients with IBD treated with UST comprise a highly refractory group, with high rates of disease activity at conception. Their pregnancy and neonatal outcomes were favorable, and comparable to those in patients treated with anti-TNF or conventional therapy.